Clausena excavata Burm. f. (Rutaceae): A review of its traditional uses, pharmacological and phytochemical properties - Arbab, I.A.; Abdul, A.B.; Aspollah, M.; Abdullah, R.; Abdelwahab, S.I.; Mohan, S.; Abdelmageed, A.H.A. (2011)
The present review describes the morphological, traditional, phytochemical and pharmacological aspects of Clausena excavata (Burm. f., Rutaceae). The plant grows wild in the tropical and subtropical parts of Asia and represents one of the richest sources of medicinal natural products. It is intensively used currently in traditional medicine for treatment of different illnesses. One part or a mixture of two or more parts of the plant in the form of powder or liquid doze is usually given to the patient. Phytochemically, many pure compounds from several secondary metabolite groups of C. excavata have been isolated from different parts of the plant including leaves, stems, stem barks, roots, root barks, rhizomes and flowers. Their chemical structures however, have been elucidated using several spectroscopic techniques. Pharmacologically, many secondary metabolites including alkaloids and coumarins have been tested for their biological activities. Anticancer, immunomodulatory, anti-HIV-1, antioxidant, antibacterialial, insecticidal, antifungal, antinociceptive, anti-malarial and antiplatelet activities of this plant have been detailed here. This paper enumerates an overview of its phytochemical and pharmacological properties, which may provide assistance to researchers to determine further, the efficacy and potency of C. excavata as medicinal plant.